2022
DOI: 10.1007/s10072-022-06051-6
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccines and patients with multiple sclerosis: willingness, unwillingness and hesitancy: a systematic review and meta-analysis

Abstract: Objective The purpose of this study was to determine the pooled prevalence of vaccination willingness, unwillingness, and hesitancy among patients with multiple sclerosis. Methods Databases including PubMed, Scopus, EMBASE, Web of Science, and Google Scholar were searched. by two expert researchers, as well as references in the included studies, which were published before October 2021. Results Three hundred eighty articles were found in four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…The current findings are consistent with those of previous meta-analyses, which estimated the prevalence of vaccine hesitancy in the general population at 26-42% [15,[80][81][82][83]. In special populations, previous meta-analyses revealed that the hesitancy for COVID-19 vaccination was estimated at 24%, 27%, and 26% in multiple sclerosis patients, older people, and healthcare students, respectively [84][85][86]. Furthermore, hesitancy to receive a COVID-19 booster was reported at 21% in the general population [87].…”
Section: Discussionsupporting
confidence: 91%
“…The current findings are consistent with those of previous meta-analyses, which estimated the prevalence of vaccine hesitancy in the general population at 26-42% [15,[80][81][82][83]. In special populations, previous meta-analyses revealed that the hesitancy for COVID-19 vaccination was estimated at 24%, 27%, and 26% in multiple sclerosis patients, older people, and healthcare students, respectively [84][85][86]. Furthermore, hesitancy to receive a COVID-19 booster was reported at 21% in the general population [87].…”
Section: Discussionsupporting
confidence: 91%
“…Similar to concerns about the rapidity of development of the vaccines seen in the general community and other chronic disease populations, our data reinforced safety and efficacy concerns balanced with COVID-19 disease and complication prevention and coupled with intersecting decision factors terms of the long-term impact on their disease [ 13 , 47 , 48 ].…”
Section: Discussionsupporting
confidence: 67%
“…In addition to the unanimous agreement that VH was a policy problem, most reviews (28/49; 57%), suggested that the problem was widespread relative to the goal of achieving quasi-total vaccine confidence / acceptance / uptake, and therefore did not study a specific demographic group. Remaining reviews focused on pregnant women (63,75,83,(85)(86)(87)(88)(89), healthcare workers (56,67,68,86,90), college students (52,56,67), racial/ethnic minorities (16,53,79), parents or guardians (48,73), older adults (61), LGBTQ+ individuals (51), and multiple sclerosis patients (91).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…41/49; 84%) presented COVID-19 as "lethal", while a small minority (8/49; 16%) did not use that word, but still implied that reported death counts (e.g., by the WHO) were higher than deaths caused by other diseases, thus reason for concern(17,47,57,66,70,85,86,91). Five reviews among those referring to COVID-19 as "lethal" (5/41; 12%) asserted that vaccines were critical to decrease COVID-specific mortality, especially among demographic groups deemed at high risk(50,52,59,65,92).…”
mentioning
confidence: 99%